2013
DOI: 10.1021/jp406878k
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Iron Carbonyl-Catalyzed Hydrogenation of Ethylene. 1. Theoretical Exploration of Molecular Pathways

Abstract: The hydrogenation of alkenes catalyzed by metal carbonyls is an intricate process involving reactions of various isomers of labile π- and σ-complexes, hydrides, dihydrides, and their radicals. Two general mechanisms have been suggested in the literature regarding the catalytic hydrogenation of simple alkenes by photochemically activated iron pentacarbonyl: a molecular mechanism that involves the sequential replacement of two carbonyl ligands by hydrogen and unsaturated ligands, and a radical mechanism involvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 90 publications
1
18
0
Order By: Relevance
“… 56 Its performance has been extensively studied for various properties and systems, including cases in the same problem domain as the work presented here. 15 , 36 , 51 , 57 59 , 64 For instance, the barrier height of the iconic BPR rearrangement in Fe(CO) 5 was computed by Harris et al at the BP86 GGA level to be 2.1 kcal mol –1 , 36 which is in remarkably good agreement to the experimental activation energy of 1.6 ± 0.3 kcal mol –1 obtained via temperature-dependent two-dimensional infrared spectroscopy. 36 While no experimental data is available for the geometries of the HFe˙(CO) 4 isomers to benchmark the employed geometry optimization approach, it is known that DFT successfully predicts the geometries of the precursor H 2 Fe(CO) 4 ( ref.…”
Section: Methods and Computational Detailssupporting
confidence: 75%
See 3 more Smart Citations
“… 56 Its performance has been extensively studied for various properties and systems, including cases in the same problem domain as the work presented here. 15 , 36 , 51 , 57 59 , 64 For instance, the barrier height of the iconic BPR rearrangement in Fe(CO) 5 was computed by Harris et al at the BP86 GGA level to be 2.1 kcal mol –1 , 36 which is in remarkably good agreement to the experimental activation energy of 1.6 ± 0.3 kcal mol –1 obtained via temperature-dependent two-dimensional infrared spectroscopy. 36 While no experimental data is available for the geometries of the HFe˙(CO) 4 isomers to benchmark the employed geometry optimization approach, it is known that DFT successfully predicts the geometries of the precursor H 2 Fe(CO) 4 ( ref.…”
Section: Methods and Computational Detailssupporting
confidence: 75%
“… 36 While no experimental data is available for the geometries of the HFe˙(CO) 4 isomers to benchmark the employed geometry optimization approach, it is known that DFT successfully predicts the geometries of the precursor H 2 Fe(CO) 4 ( ref. 58 and 59 a ) and various open-shell derivatives of the HFe˙(CO) 4 radical (a review can be found in ref. 15 ).…”
Section: Methods and Computational Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, the Glaser-Tilley type mechanism is excluded because the model silane SiR 3 H (R -H) is not possible to form the metal silylene species. Very recently, Asatryan and Ruckenstein [38] have investigated the detailed mechanism of iron carbonyl-catalyzed hydrogenation of ethylene using DFT methods. The water gas shift reaction catalyzed by M(CO) 5 (M = Fe, Ru, Os) has been studied by density functional theory and ab initio calculations [39].…”
Section: Introductionmentioning
confidence: 99%